Kadar Hemoglobin pada Pasien Gagal Ginjal Kronis Sesudah Menjalani Hemodialisa - Cici Farhana Ambarwanty Mohtar; Esa Dhiandani; Suci Indah Budiarti; Martha Intan Nagari Pratiwi (Universitas Muhamadiyah Manado, 2021)
Chronic Kidney Diseases (CKD) is a disease condition where there is a decrease in kidney function, no longer able to carry out its function of filtering the blood, removing toxins and unable to remove waste products from the blood effectively, characterized by the presence of protein in the urine and a decrease in the glomerular filtration rate. Hemodialysis is a kidney replacement therapy method that is often used to manage CKD. The prevalence of CKD in Indonesia continues to increase every year with some patients undergoing hemodialysis. CKD patients undergoing HD are susceptible to anemia. Anemia in CKD patients can be caused by blood loss during dialysis procedures, and disturbances in iron metabolism. The aim of the study was to analyze changes in hemoglobin levels in CKD patients after undergoing hemodialysis. The research was carried out in a descriptive observational manner through an initial screening stage, an examination stage by measuring hemoglobin levels before and after the hemodialysis session and readings using a Mindray BC-5830. The examination results showed that the hemoglobin levels of CKD patients increased after undergoing HD. Hemoglobin levels in male CKD patients were higher than female patients both before and after undergoing HD. The conclusion of this study is that HD has an effect on increasing hemoglobin levels in CKD patients, both female and male patients.